(NiNSTRUMENTALXNYJ KONCERTs - (NtARAKANOW(B. (Nm(B. (Ne(B.s ((NmOSKWAs (NzNANIEs, 1986)
(Nw BRO[@RE RASSMATRIWA@TSQ OSNOWNYE \TAPY STANOWLENIQ I RAZWITIQ ODNOGO IZ WEDU]IH VANROW(B.s
Keywords: (NISTORIQs